PHOSPHATIDIC ACID LIPOSOMES AS MINERALIZING SURFACES: KINETICS AND ENERGETICS - Kraus B.L.; Crenshaw M.A. (My University, 1996)
Acidic macromolecules have consistently been associated with biological mineral formation in vivo. Several of these macromolecules have been shown to induce mineral formation from metastable solutions when attached to a substrate. However, when free in solution, the same molecules inhibit mineral formation. These results indicate that the surface plays an important role in biomineralization. We have used phosphatidic acid liposomes as model surfaces to evaluate the role of the surface in the kinetics of mineral formation. We determined the effect of lipid concentration and solution supersaturation on the induction time (time before detectable mineral formation). Lipid concentrations from 15 to 0.7 μM showed increased induction times with decreasing lipid concentrations. The rate of mineral induction was linear with lipid concentration at low concentrations, but appeared to saturate at high lipid concentrations. Decreasing the solution supersaturation resulted in increased induction times. Using the supersaturation data, the interfacial tension for mineral induction on phosphatidic acid liposomes was determined to be 295 erg/cm2. This value may reflect the energetics of heterogeneous nucleation on a highly phosphorylated surface.